Economic Importance Of The Belgian Ports: Flemish maritime ports, Liège port complex and the port of Brussels – Report 2013 - Frank Van Nieuwenhove (National Bank of Belgium, 2015)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper1 provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2008 - 2013, with an emphasis on 2013. Focusing on the three major variables of value added, employment and investment, the report also provides some information based on the social balance sheet and an overview of the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. As a result of the underlying calculation method the changes of indirect employment and indirect value added can differ from one another. The developments concerning economic activity in the six ports in 2012 - 2013 are summarised in the table on the next page. The overall decline in maritime traffic seen in the Flemish maritime ports in general in 2012, and in each individual port, was reversed in 2013, but only thanks to growth in Antwerp; the other three ports (Ghent, Ostend and Zeebrugge) experienced a further decrease. In terms of value added, the opposite occurred: a general increase, except in Antwerp, resulting in a slight rise for these ports as a whole. The employment picture was variable, but there was expansion overall, matching the growth of value added, namely 0.3 %. Finally, investment in the Flemish ports declined overall, totalling 3.2 % less in 2013 than in the previous year. In the ports of Liège and Brussels, cargo traffic and employment both declined in 2013. After the sharp fall in 2012, value added at the port of Liège edged upwards again, but in Brussels it recorded a significant decline2. Conversely, investment in Liège was down again, following the surge in 2012, whereas the port of Brussels saw a substantial increase. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2013.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport; intermodality; public investments